Rightward Movement Phenomena in Linguistics - Kamada, Kohji (Cambridge Scholars Publishing, 2018)
This book demonstrates that some properties of rightward movement phenomena (a cover term referring to sentences in which an element appears to be "displaced" to the right) may be derived from syntactic principles and interface conditions within the framework of the generative grammar/minimalist program. It also argues that certain properties, which up to now have been dealt with purely in regards to syntax, can be better accounted for in terms of language processing; accordingly, the human parser should undertake explanations of part of the competence system's output.The volume's analysis of rightward movement phenomena leads to the conclusion that phrasal rightward movement rules in syntax fail to follow specific principles. At first glance, this conclusion seems identical with Kayne's (1994) claim that no rightward movement rules exist. However, this work provides completely different grounds for the absence of rightward movement rules, meaning that it presents an original view of rightward movement phenomena.